2018
DOI: 10.1111/ijpo.12291
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal pre‐pregnancy overweight on infant overweight at 1 year of age: associations and sex‐specific differences

Abstract: Maternal pre-pregnancy OWOB increases the risk of infant overweight, and this association is more evident in male infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 25 publications
1
28
1
1
Order By: Relevance
“…In contrast, placenta from obese women with a male fetus contain increased amounts of carbonyls and nitrotyrosine, and as a potential compensatory mechanism, these placenta have elevations in glutathione peroxidase and thioredoxin reductase activity. The collective findings from this latter study reveal that the placenta of males derived from lean mothers possess the greatest antioxidant activity, but such protective responses are abolished with maternal obesity, which may account for later adverse outcomes in sons, in particular those born to obese mothers (Bridgman et al, 2018; Greene‐Cramer et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
“…In contrast, placenta from obese women with a male fetus contain increased amounts of carbonyls and nitrotyrosine, and as a potential compensatory mechanism, these placenta have elevations in glutathione peroxidase and thioredoxin reductase activity. The collective findings from this latter study reveal that the placenta of males derived from lean mothers possess the greatest antioxidant activity, but such protective responses are abolished with maternal obesity, which may account for later adverse outcomes in sons, in particular those born to obese mothers (Bridgman et al, 2018; Greene‐Cramer et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
“…While the relationship between maternal weight status and BP in early postpartum has not been examined in relation to infant weight gain, the influence of maternal weight status before and during pregnancy—and the influence of maternal BP during pregnancy—have been examined separately in relation to infant weight gain. For example, studies have shown that maternal obesity before pregnancy presented a two to threefold increase in overweight risk at ages 12 and 24 months, while excessive maternal weight gain during pregnancy presented a fourfold increase in overweight risk at age 36 months . In one of the few studies to have examined maternal weight status after pregnancy, Robinson and colleagues found that greater maternal weight gain within 13 months postpartum was associated with increased odds of overweight at age 5 years .…”
Section: Discussionmentioning
confidence: 99%
“…Mothers may influence infant weight gain through shared genetics, environments, and behaviours . Of note, maternal obesity has been examined in relation to infant obesity risk: Mothers who were classified as obese before pregnancy (body mass index [BMI] greater than or equal to 30 kg/m 2 ) were more likely to have a child classified as obese (BMI greater than 97th percentile) within 2 years of age . Furthermore, mothers with excessive weight gain during pregnancy were more likely to have a child classified as overweight (BMI greater than or equal to 95th percentile) at 3 years of age .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…alimentação infantil, sobretudo pela maior relação com o preparo das refeições e escolha dos alimentos(VICARI, 2013;BARROS; SEYFFARTH, 2008).Apesar da atual reestruturação da rotina familiar especialmente pelo novo papel desempenhado pela mulher no mercado de trabalho, a mãe continua representando a principal provedora da alimentação da família(REICHEMBACH, 2004), sendo a mais predominante interlocutora envolvida na díade criança-ambiente (ENGSTRON; ANJOS, 1999). fatores podem interferir na saúde e qualidade de vida, sendo capazes de provocar impactos não apenas na infância, como também na idade adulta.O sobrepeso e a obesidade materna pré-gestacional foram associados com o aumento do risco de excesso de peso infantil no primeiro ano de vida(BRIDGMAN et al, 2018). Um estudo avaliou o curso do IMC dos dois aos seis anos de idade e notou valores mais elevados, bem como na trajetória de aumento, entre crianças de mães com excesso de peso no período anterior à gestação e nos filhos das que apresentaram ganho de peso gestacional acima do recomendado(WANG et al, 2019).…”
unclassified